Steps:
Group like terms:
8p - 3 + 9p + 6p + 2p - 6p - 3p - 9p-3
Add similar elements:
8p - 3 + 9p + 6p + 2p - 6p - 3p - 9p = 7p
=7p−3
Answer: =7p−3
Please mark brainliest
Hope this helps.
Answer:
7p-3
Step-by-step explanation:
We are given the expression:
8p - 3 + 9p + 6p + 2p - 6p - 3p - 9p
To simplify, we can combine like terms. Add all the terms with a variable, then add the terms without a variable.
(8p + 9p + 6p + 2p - 6p - 3p - 9p)+ -3
(25p -18p) -3
7p-3
Answer:vf
Step-by-step explanation:
Step-by-step explanation:
(r/s)(x)=3x-1
2x
(r/s)(6)=18-1/12
=17/12
Answer:
y = -x - 7
Step-by-step explanation:
As we move from the point (3, -4) to the point (5, -6), x increases by 2 and y decreases by 2. Thus, the slope of this line is m = rise / run = -2/2, or -1.
Starting with the general slope-intercept form of the equation of a straight line, we get y = mx + b => y = -1x + b.
Subbing -4 for y and 3 for x, we get
-4 = -1(3) + b, which yields b = -1
Thus, the desired equation is
y = -x - 1